Pendidikan Kristiani yang Kreatif Berbasis Limbah Karton sebagai Upaya Pelestarian Lingkungan dan Pengembangan Sosial-Emosional Anak - Winantu Winantu; Maria Gabriela Tires; Natalia Kafiar (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to describe the implementation of environmental conservation through cardboard waste-based learning and its impact on the social-emotional development of early childhood students at PAUD Kelas Indria, Gereja Kemah Injil Indonesia, Sorong City. This study used a qualitative approach with a descriptive research design. The findings indicate that cardboard waste-based learning can integrate environmental conservation values into children's learning activities through creative and collaborative activities. In addition, these activities contribute to the development of children’s social-emotional aspects, such as cooperation, responsibility, empathy, and self-confidence. Therefore, cardboard waste-based learning can serve as an effective alternative learning strategy for fostering environmental awareness while simultaneously developing the social-emotional skills of early childhood learners.